Mechanistic insights into β-lactamase-catalysed carbapenem degradation through product characterisation - Lohans, C; Freeman, E; Van Groesen, E; Tooke, C; Hinchliffe, P; Spencer, J; Brem, J; Schofield, C (Nature Research, 2019)
β-Lactamases are a major threat to the clinical use of carbapenems, which are often antibiotics of last resort. Despite this, the reaction outcomes and mechanisms by which β-lactamases degrade carbapenems are still not fully understood. The carbapenem bicyclic core consists of a β-lactam ring fused to a pyrroline ring. Following β-lactamase-mediated opening of the β-lactam, the pyrroline may interconvert between an enamine (2-pyrroline) form and two epimeric imine (1-pyrroline) forms; previous crystallographic and spectroscopic studies have reported all three of these forms in the contexts of hydrolysis by different β-lactamases. As we show by NMR spectroscopy, the serine β-lactamases (KPC-2, SFC-1, CMY-10, OXA-23, and OXA-48) and metallo-β-lactamases (NDM-1, VIM-1, BcII, CphA, and L1) tested all degrade carbapenems to preferentially give the Δ² (enamine) and/or (R)-Δ¹ (imine) products. Rapid non-enzymatic tautomerisation of the Δ² product to the (R)-Δ¹ product prevents assignment of the nascent enzymatic product by NMR. The observed stereoselectivity implies that carbapenemases control the form of their pyrroline ring intermediate(s)/product(s), thereby preventing pyrroline tautomerisation from inhibiting catalysis.